2011
DOI: 10.2495/sdp-v6-n2-152-165
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on alternative CFRP retrofitting applications of heritage structures

Abstract: It is crucial for masonry structures of historical value to increase their seismic performances in order to be protected against earthquakes. The damages to the masonry structures might be attributed to insuffi cient soil properties, non-conformity with relevant regulations, design and application defects and wear. This study experimentally investigates the strengthening of the masonry structures on one side as historical structural walls can only be strengthened on one side in most cases. In the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the Torunbalci et al study, the increase in the load-bearing capacities of the one-sided reinforced wall samples was approximately 100%. On the other hand, this ratio was 135% on average for the one-sided reinforced wall that had previously been damaged [17]. Parisi et al indicate that FRCM systems applied to URM walls subjected to diagonal compression can result in a shear strength increase ranging from 36% to 441%, along with an increase in pseudo-ductility ranging from 10% to 130%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Torunbalci et al study, the increase in the load-bearing capacities of the one-sided reinforced wall samples was approximately 100%. On the other hand, this ratio was 135% on average for the one-sided reinforced wall that had previously been damaged [17]. Parisi et al indicate that FRCM systems applied to URM walls subjected to diagonal compression can result in a shear strength increase ranging from 36% to 441%, along with an increase in pseudo-ductility ranging from 10% to 130%.…”
Section: Resultsmentioning
confidence: 99%
“…The findings revealed that unreinforced brick wall specimens exhibited brittle behavior, whereas the performance of the brick wall specimens reinforced with CFRPs exhibited improvements in terms of strength ratings and energy dissipation capacities. Notably, the enhancements in the structural brick wall specimens were more significant when the reinforcement was applied to the entire surface of the wall in textile form rather than in strip form [17]. Garcia et al conducted an experimental investigation to examine the behavior of masonry walls reinforced with single-and double-layer steel-reinforced lime mortar (SRG).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of improvement depends on the ratio of FRP, the cost rises with the greater quantity of FRP used. Glass Fiber Reinforced Polymer (GFRP) and Carbon Fiber Reinforced Polymer (CFRP) as retro tting materials for masonry walls have been investigated, utilizing various techniques including full surface, strips, and near surface-mounted installations (NSM) [16][17][18][19][20] . The full surface application of GFRP and CFRP fabrics exhibited a greater improvement in shear strength compared to strips cut from fabrics 17,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Glass Fiber Reinforced Polymer (GFRP) and Carbon Fiber Reinforced Polymer (CFRP) as retro tting materials for masonry walls have been investigated, utilizing various techniques including full surface, strips, and near surface-mounted installations (NSM) [16][17][18][19][20] . The full surface application of GFRP and CFRP fabrics exhibited a greater improvement in shear strength compared to strips cut from fabrics 17,20 . A typical failure mode of this method involves debonding between the FRP layer and the wall surface.…”
Section: Introductionmentioning
confidence: 99%